Factors influencing the elderly’s adoption of mHealth: an empirical study using extended UTAUT2 model - Jahir Uddin, P.; Sorwar, G.; Rakibul Hoque, M.D.; Achchuthan, S. (BMC Medical Informatics and Decision Making, 2022)
Despite the high usage of mobile phones in daily life in developing countries like Bangladesh, the adoption and usage of mHealth services have been signifcantly low among the elderly population. When searching previous studies, the researchers have found that no studies have empirically investigated whether the quality of life and service quality are signifcant for mHealth adoption by elderlies in Bangladesh. Hence, this study aimed to extend the Unifed Theory of Acceptance and Use of Technology by adding service quality and the quality of life to empiri- cally fnd the key factors that infuence elderlies’ intention to adopt and use mHealth services in Bangladesh.
Keywords: mHealth; Elderly; UTAUT2; Quality of Life; Service quality; Develop country